Analisis Penerapan Kurikulum ABRSM terhadap Kemampuan Anak Usia 5–12 Tahun dalam Pembelajaran Piano Klasik di Crescendo Musik Course BALI - Ni Kadek Nonik Dwi Putri; Guntur Eko Prasetyo; Ni Made Ayu Dwara Putri (Institut Seni Indonesia Denpasar, 2026)
Purpose: This study aims to analyze the implementation of the ABRSM curriculum in relation to the piano performance abilities of children aged 5–12 years at Crescendo Music Course Bali. Method: This study employs a data triangulation approach, incorporating observations, interviews, and surveys conducted with instructors, students, and parents. Result and Discussion: The findings indicate that age does not directly determine a student’s piano grade level. Instead, several other factors play a more significant role in shaping students’ development, including the intensity of independent practice at home, active parental involvement, and the child’s intrinsic motivation in learning piano. Furthermore, the implementation of the ABRSM curriculum, when adapted to the individual characteristics and needs of each student, has been shown to effectively enhance technical skills, musicality, and self-confidence. Implication: These results highlight the importance of a personalized pedagogical approach in music education, emphasizing not only structured curricula but also the supporting ecosystem surrounding the student. Future research is recommended to further explore long-term learning outcomes and the role of socio-cultural factors in shaping children’s musical development.